2021
DOI: 10.20944/preprints202110.0250.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nontuberculous Mycobacteria Prevalence in Bats’ Guano from Caves and Attics of Buildings Studied by Culture and qPCR Examinations

Abstract: A total of 281 guano samples were collected from caves (N = 181) in 8 European countries (Bulgaria, Czech Republic, France, Hungary, Italy, Romania, Slovakia and Slovenia) and attics in the Czech R. (N = 100). The correlation of detection of mycobacteria between Ziehl-Neelsen (ZN) microscopy and culture examination and qPCR was strong. ZN microscopy was positive in guano from caves (58.6%) more than double than positivity in guano from attics (21.0%; P <0.01). From 89 mycobacterial isolates (73 isol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
4
0
5
Order By: Relevance
“…There is a lack of knowledge about the presence of mycobacteria in bats (Modra et al, 2017;Pavlik et al, 2021;Ulmann et al, 2021;Pavlik et al, 2022).…”
Section: Superfamilia Noctilionoideamentioning
confidence: 99%
See 3 more Smart Citations
“…There is a lack of knowledge about the presence of mycobacteria in bats (Modra et al, 2017;Pavlik et al, 2021;Ulmann et al, 2021;Pavlik et al, 2022).…”
Section: Superfamilia Noctilionoideamentioning
confidence: 99%
“…(Muhldorfer, 2012). Hay una carencia de conocimiento sobre la presencia de micobacterias en murciélagos (Modra et al, 2017;Pavlik et al, 2021;Ulmann et al, 2021;Pavlik et al, 2022).…”
Section: Superfamilia Noctilionoideaunclassified
See 2 more Smart Citations
“…Chloroflexi, Planctomycetes, Bacteroidetes, Firmicutes, Acidobacteria, Nitrospirae, Gemmatimonadetes, and Verrucomicrobia also accounted for large proportions of the total microbial community in caves (Wu et al, 2015;Zhu et al, 2019). In some organic cave samples such as biofilms in sulfur cave, bat guanos, spiders' webs and earthworm castings, Mycobacterium was prevalently detected (Modra et al, 2017;Sarbu et al, 2018;Hubelova et al, 2021;Pavlik et al, 2021). Over 500 genera of fungi, such as Penicillium, Aspergillus and Mortierella have been reported in caves (Vanderwolf et al, 2013), and new fungal species were identified from cave air, rock, sediment and water samples (Zhang et al, 2017(Zhang et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%